Fundamentals of atomic and close-to-atomic scale manufacturing: a review. (3rd December 2021) - Gao, Jian; Luo, Xichun; Fang, Fengzhou; Sun, Jining
Abstract: Atomic and close-to-atomic scale manufacturing (ACSM) represents techniques for manufacturing high-end products in various fields, including future-generation computing, communication, energy, and medical devices and materials. In this paper, the theoretical boundary between ACSM and classical manufacturing is identified after a thorough discussion of quantum mechanics and their effects on manufacturing. The physical origins of atomic interactions and energy beams-matter interactions are revealed from the point view of quantum mechanics. The mechanisms that dominate several key ACSM processes are introduced, and a current numerical study on these processes is reviewed. A comparison of current ACSM processes is performed in terms of dominant interactions, representative processes, resolution and modelling methods. Future fundamental research is proposed for establishing new approaches for modelling ACSM, material selection or preparation and control of manufacturing tools and environments. This paper is by no means comprehensive but provides a starting point for further systematic investigation of ACSM fundamentals to support and accelerate its industrial scale implementation in the near future.